Non-endometrioid and high-grade endometrioid endometrial cancers show DNA fragmentation factor 40 (DFF40) and B-cell lymphoma 2 protein (BCL2) underexpression, which predicts disease-free and overall survival, but not DNA fragmentation factor 45 (DFF45) underexpression - Banas, Tomasz (BMC Cancer, 2018)
BACKGROUND: The expression of DNA fragmentation factor 45 (DFF45) and B-cell lymphoma 2 (BCL2) in glands of the normal human endometrium is related to phases of the menstrual cycle and decreases after menopause, whereas the expression of DNA fragmentation factor 40 (DFF40) is stable. Moreover, DF45, BCL2 and DFF40 underexpression has been reported in numerous malignancies, including uterine leiomyosarcomas. In this study, we aimed to investigate DFF45, BCL2 and DFF40 expression in endometrioid and non-endometrioid types of endometrial cancers (ECs). We also evaluated the correlations between DFF45, BCL2 and DFF40 expression levels and clinicopathological parameters and determined the value of these three proteins as prognostic markers of disease-free survival (DFS) and overall survival (OS). METHODS: Immunohistochemistry was performed to evaluate DFF45, BCL2 and DFF40 expression in 342 cases of ECs. Student’s t-test, the Mann-Whitney U-test, and the chi-squared test were used for the statistical analyses as appropriate. The Cox-Mantel test, Cox’s proportional hazard model, and relative risk analyses were used to evaluate associations between DFF40, DFF45, and BCL2 expression and clinicopathological characteristics. RESULTS: DFF40 and BCL2, but not DFF45, were significantly underexpressed in non-endometrioid and high-grade endometrioid ECs compared with low- and moderate-grade endometrioid ECs. Women with DFF40- and BCL2-negative tumors had higher risks of disease recurrence, lymph node involvement, lympho-vascular space infiltration, and deep myometrial invasion compared with women with DFF40- and BCL2-positive tumors. Additionally, women with DFF40- and BCL2-negative tumors had significantly lower OS and DFS than women with DFF40- and BCL2-positive tumors. A multivariable analysis of the model, including the clinicopathological characteristics and immunohistochemical results, showed that negative BCL2 expression, lymph node involvement, and high-stage and high-grade disease were independent predictors of OS, whereas negative BCL2 expression, lymph node involvement, and high-stage disease were independent predictors of DFS. CONCLUSIONS: Compared with low- and moderate-grade endometrioid ECs, non-endometrioid and high-grade endometrioid ECs showed significant DFF40 and BCL2 underexpression. The absence of DFF40 and BCL2 expression negatively affects DFS and OS. Further prospective studies are warranted to assess the potential utility of DFF40 and BCL2 as targets in the diagnosis or treatment of ECs.